Educational and Scholarly Activity of K. Rickevičiūtė - Juršėnas, Nikodemas (Problemos, 1988)
The article deals with educational and scholarly activity of the Lithuanian philosopher K. Rickevičiūtė (1922-1984). The philosopher is presented as an interesting and original person and an experienced professor. The scientific aspect of her activity• is discussed too and the main achievements in the fields of logic, of philosophy, and ethics are pointed out.